Laimarela Sekaniṃ amasuṃ Khamamoi Ẏāṃmoi - Gauracandra, Maẏāṃlambama; Ibobī, Nāorema (Gauracandra amasuṃ Ibobī, 1975)
Manipuri mythical beliefs about the origin and death of man, attributed to Laimarela Sekaniṃ, goddess of creation and Khammamoi Ẏāṃmoi, goddess of death; transcribed from an old Manipuri chronicle (puya)